2019
DOI: 10.1016/j.wasman.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

An analyses of the status of landfill classification systems in developing countries: Sub Saharan Africa landfill experiences

Abstract: Municipal solid waste (MSW) management remains a challenge in developing countries due to increasing waste generation, high costs associated with waste management and the structure of the containment systems implemented. This study analyses the classification of landfilling systems by using documented cases reported mainly in publications in waste management in relation to nonengineered landfilling systems/approved dumpsites in Sub Saharan African (SSA) countries from 2000 to 2018. The work identifies an exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(59 citation statements)
references
References 55 publications
1
58
0
Order By: Relevance
“…Another major setback is that the ministry's guideline recommends landfilling as a method of final waste disposal but was silent on the modalities for landfill construction and operation, whether at the present or in the future. However, a recent study has demonstrated that many landfills in developing countries (Nigeria inclusive) are non-engineered, which makes it quite difficult to harness the waste resources into valuable products for commercialization [34].…”
Section: Current Waste Management Framework In Nigeria: Brief Overviewmentioning
confidence: 99%
“…Another major setback is that the ministry's guideline recommends landfilling as a method of final waste disposal but was silent on the modalities for landfill construction and operation, whether at the present or in the future. However, a recent study has demonstrated that many landfills in developing countries (Nigeria inclusive) are non-engineered, which makes it quite difficult to harness the waste resources into valuable products for commercialization [34].…”
Section: Current Waste Management Framework In Nigeria: Brief Overviewmentioning
confidence: 99%
“…Not only domestic solid waste, but also their incineration fly ash, was filled in the west of this landfill. Considering various historical factors, this landfill excluded an impermeable artificial system as well as leachate drainage facilities [21]. Three waste dams, the leachate collection pond and the pretreatment station at the eastern side of the landfill were not built until the end of 2007, as seen in Figure 2, and the pretreatment station, with a capacity for 70 m 3 /day, was abandoned in January 2015.…”
Section: Site History and Conditionmentioning
confidence: 99%
“…Landfilling, incineration and illegal dumping are the dominant methods of dealing with waste in many African countries (Achankeng, 2003, Williams, 2005, Zoeteman et al, 2010, Kazuva and Zhang, 2019, Kyere et al, 2019, and Oelofse and Nahman et al, 2019. A plethora of scholars (McKay, 2002, Hicks, 2007, Hristovski et al, 2007, Smyth et al, 2010, Topanou et al, 2011, Badgie et al, 2012, and Idowu, 2019 have cited the issue of poor waste characterisation as a major stumbling-block to waste management in Africa. Topanou et al (2011) argue that waste characterisation remains the key prerequisite for effective waste management programs.…”
Section: Introductionmentioning
confidence: 99%